2013
DOI: 10.1038/ncb2797
|View full text |Cite
|
Sign up to set email alerts
|

ULK1 targets Beclin-1 in autophagy

Abstract: The substrates of mammalian ULK1/2 and its yeast homologue Atg1 in autophagy have remained elusive. The class III phosphatidylinositol 3-kinase component Beclin-1 has now been identified as a physiological substrate of the ULK kinases in autophagy following amino acid starvation, therefore suggesting a critical molecular link between the upstream kinases and the autophagy core machinery.Autophagy is a specialized degradative route, which starts with the formation of autophagosomes and ends in the lysosomes, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 15 publications
3
58
0
Order By: Relevance
“…The autophagyrelated (ATG) proteins compose several core components of autophagy, which are required for autophagosome formation (24,25). mTORC1 (mammalian target of rapamycin complex 1) kinase is a key negative regulator of the ULK1 complex (Unc-51-like autophagy activating kinase 1), which is made up of ULK1, ATG101, ATG13, and RB1CC1/FIP200 (26)(27)(28)(29)(30) and serves as the initiator in the autophagic cascade. The class III phosphatidylinositol 3-kinase (PI3K) complex (BECN1/Beclin1-ATG14-VPS15-VPS34) and two other conjugation systems, ATG12 (ATG12-ATG5-ATG16) and LC3/ATG8, operate downstream of ULK-1 (31,32).…”
mentioning
confidence: 99%
“…The autophagyrelated (ATG) proteins compose several core components of autophagy, which are required for autophagosome formation (24,25). mTORC1 (mammalian target of rapamycin complex 1) kinase is a key negative regulator of the ULK1 complex (Unc-51-like autophagy activating kinase 1), which is made up of ULK1, ATG101, ATG13, and RB1CC1/FIP200 (26)(27)(28)(29)(30) and serves as the initiator in the autophagic cascade. The class III phosphatidylinositol 3-kinase (PI3K) complex (BECN1/Beclin1-ATG14-VPS15-VPS34) and two other conjugation systems, ATG12 (ATG12-ATG5-ATG16) and LC3/ATG8, operate downstream of ULK-1 (31,32).…”
mentioning
confidence: 99%
“…However, in our study, we found that increased TXNIP had no influence on AMPK phosphorylation. Beclin 1 also has a central role in autophagy, by interacting with Vps34 to induce autophagy . We found that overexpression of TXNIP had no impact on Beclin 1 expression.…”
Section: Discussionmentioning
confidence: 68%
“…In mammals a direct phosphorylation interaction between ULK1/Atg1 and Beclin 1 was recently found, strengthening further the importance of Beclin 1 in autophagy induction30. As Beclin 1 could serve as an alternative autophagy inducer in non-unikont protists, we searched for and could identify possible Beclin 1 orthologs in the half of these species (Suppl.…”
Section: Resultsmentioning
confidence: 77%